The Institutions of Programmatic Action Policy Programs in French and German Health Policy - Hornung, Johanna; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
(3z(BThe Programmatic Action Framework (PAF) is the newcomer in the pluralistic set of the theories of the policy process." -Giliberto Capano, Professor of Political Science and Public Policy, University of Bologna, Italy (3z(BThe book presents empirical cross-country evidence for the PAF's idea that overlapping biographies of policy actors and resulting social identities often drive collective action.(3y (B-Tanya Heikkila, Professor of Public Affairs, University of Colorado Denver, USA (3z(BThis work advances knowledge of programmatic actors comparatively.(3y (B-Michael Howlett, Burnaby Mountain Professor, Simon Fraser University, Canada (3z(BJohanna Hornung shows that policy change is irrevocably linked to the programmatic group, framed by two specific institutions - the recruitment processes and career paths of administrative actors.(3y (B-Sabine Saurugger, Professor of Political Science, Science Po Grenoble, France. This open access book is thefirst monograph to systematically apply the Programmatic Action Framework (PAF) in a comparative analysis of public policy in two institutionally different countries. The PAF seeks to explain long-term policy change by examining the shared biographies of policy actors who, to foster their careers, coalesce around policy programs which they promote throughout the policy process. Comparing health policy-making in France and Germany between 1990 and 2020, the book sheds light on the institutional settings that are necessary for programmatic action to occur. It will appeal to scholars and students of public policy, public administration, and health policy. Johanna Hornung is a Research Associate at the Institute of Comparative Politics and Public Policy, TU Braunschweig, Germany.s
Chapter 1: Introduction -- Chapter 2: Programmatic Action and Policy Processes -- Chapter 3: Political Institutions and Public Policy -- Chapter 4: Health Policy Institutions in France and Germany -- Chapter 5: Programmatic Action in French Health Policy -- Chapter 6: Programmatic Action in German Health Policy -- Chapter 7: The Institutions of Programmatic Action -- Chapter 8: Conclusion.
Keywords: Political planning; Comparative government; Medical policy; Public Policy; Comparative Politics; Health Policy